2000
DOI: 10.4049/jimmunol.165.12.7224
|View full text |Cite
|
Sign up to set email alerts
|

Basophil Responses to Chemokines Are Regulated by Both Sequential and Cooperative Receptor Signaling

Abstract: To investigate human basophil responses to chemokines, we have developed a sensitive assay that uses flow cytometry to measure leukocyte shape change as a marker of cell responsiveness. PBMC were isolated from the blood of volunteers. Basophils were identified as a single population of cells that stained positive for IL-3Rα (CDw123) and negative for HLA-DR, and their increase in forward scatter (as a result of cell shape change) in response to chemokines was measured. Shape change responses of basophils to che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 65 publications
(39 reference statements)
2
69
0
1
Order By: Relevance
“…Eotaxin/CCL11, a natural antagonist of CCR2, was recently shown to induce signal transduction via the ERK-1/2 pathway (30). Human basophils also express CCR2 (31) and can be activated via CCR2, resulting in shape changes (31) and the release of cytokines and leukotriene C 4 (32).…”
Section: Discussionmentioning
confidence: 99%
“…Eotaxin/CCL11, a natural antagonist of CCR2, was recently shown to induce signal transduction via the ERK-1/2 pathway (30). Human basophils also express CCR2 (31) and can be activated via CCR2, resulting in shape changes (31) and the release of cytokines and leukotriene C 4 (32).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is unclear how basophils might be recruited selectively to sites of allergic inflammation. In a recent study we showed that responses of basophils to certain CC-chemokines were different from those of other leukocytes as a result of their unique expression of multiple chemokine receptors, which can function cooperatively or sequentially (19). However, there may be more specific mechanisms or mediators that bring about the selective recruitment of basophils to sites of allergic inflammation.…”
Section: Identification Of Selective Basophil Chemoattractants Inmentioning
confidence: 99%
“…This assay, which has been adapted to measure responses of human basophils (19), in addition to eosinophils, neutrophils, and monocytes (20), is highly sensitive, detecting responses to Ͻ100 pM eotaxin-1/CCL11, and is therefore a useful tool for identifying leukocyte-stimulating activity in extracts of inflamed tissue. We have used this assay to investigate nasal polyp tissue, using a similar strategy to that used previously to identify eotaxin-1/CCL11 (21).…”
Section: Identification Of Selective Basophil Chemoattractants Inmentioning
confidence: 99%
See 2 more Smart Citations